2010
DOI: 10.1162/jocn.2009.21387
|View full text |Cite
|
Sign up to set email alerts
|

“Virus and Epidemic”: Causal Knowledge Activates Prediction Error Circuitry

Abstract: Knowledge about cause and effect relationships (e.g., virus-epidemic) is essential for predicting changes in the environment and for anticipating the consequences of events and one's own actions. Although there is evidence that predictions and learning from prediction errors are instrumental in acquiring causal knowledge, it is unclear whether prediction error circuitry remains involved in the mental representation and evaluation of causal knowledge already stored in semantic memory. In an fMRI study, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
3
13
0
2
Order By: Relevance
“…The difference waves mainly activated the central and central-parietal sites. These results suggested that the representation of causal judgment involved more cognitive resources than associative judgment, complementary with behavior and fMRI studies (Fenker et al, 2010;Fugelsang & Dunbar, 2005;Satpute et al, 2005). That is, people appeared to distinguish the roles of cause and effect or bind the relevant events into the 'cause' and 'effect' roles in the representation of causal relations, but such distinction was not found in the representation of associative relations .…”
Section: The Late Erp Component: Causal Judgment Versus Associative Jmentioning
confidence: 53%
See 4 more Smart Citations
“…The difference waves mainly activated the central and central-parietal sites. These results suggested that the representation of causal judgment involved more cognitive resources than associative judgment, complementary with behavior and fMRI studies (Fenker et al, 2010;Fugelsang & Dunbar, 2005;Satpute et al, 2005). That is, people appeared to distinguish the roles of cause and effect or bind the relevant events into the 'cause' and 'effect' roles in the representation of causal relations, but such distinction was not found in the representation of associative relations .…”
Section: The Late Erp Component: Causal Judgment Versus Associative Jmentioning
confidence: 53%
“…Following this, these researchers also investigated the neural basis of causal relations via fMRI (Fenker et al, 2010;Satpute et al, 2005). For example, Satpute et al (2005) found that causal judgments, in contrast to associative judgments, recruited greater activation in the left dorsolateral prefrontal cortex and the right precuneus related to working memory and reasoning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations